Synthesis and characterization of molecularly imprinted polymer for removal of 2,4-dinitrophenol - Zakaria, Nor Dyana (2010)
In this work, molecular imprinted polymers (MIPs) were prepared by bulk polymerization method in acetonitrile using 2,4-dinitrophenol, acrylamide,ethylene glycol dimethacrylate, and benzoyl peroxide as template, functional monomer, cross-linker and initiator, respectively. The functional monomer and the cross linker (molar ratio of functional monomer to cross linker 1:3) and 1.6 mmol of the initiator BPO were used. Then, the polymer were crushed, ground and sieved to obtain regularly sized particles between 80-100 μm. The polymer obtained is then washed to remove the template using methanol/ acetic acid in 2:1 (v/v) ratio for 3 times. Membrane MIP was prepared by hybridization of MIP particle with cellulose acetate (CA) and polystyrene (PS), respectively. Sorption process for the removal of 2,4-dinitrophenol using the fabricated MIP was evaluated under various pH and time conditions. Parameters studied for the removal of 2,4-dinitrophenol include sorption kinetics, sorption isotherm, selectivity and reusability of the MIP and membrane MIP. The concentration of 2,4-dinitrophenol was analyzed using UV-Vis Spectrophotometer. The prepared MIP was characterized using Fourier transformed infrared (FTIR) spectroscopy,scanning electrode microscopy (SEM), thermo gravimetric analysis (TGA),particle size analyzer (PSA) and brunauer, emmett teller (BET) adsorption isotherm analysis. The FTIR spectra showed a broadening at 3400 cm-1 indicating that a hydrogen bond interaction takes place between the phenolic hydroxyl group and the carbonyl from the amide group. From the surface morphology of SEM image, MIP could be seen to exhibit a more porous and rough structure than MIP before extraction and NIP. The surface area of the MIP is 103.65 m2/g and the NIP is 8.99 m2/g. The results showed a type IV adsorptiondesorption isotherm, which is typically characteristic of mesoporous materials. The size of the MIP particles was in the range of 130.00 nm and the particles size of non imprinted polymer (NIP) was in the range 400.00 nm. The maximum sorption of 2,4-dinitrophenol by MIP was found to be 2.88 mg/g under acidic conditions at pH 6.0. The maximum sorption of 2,4-nitrophenol by the fabricated cellulose acetate membrane with molecular imprinted polymer (CA-MIP) and polystyrene membrane with molecular imprinted polymer (PS-MIP) were found at pH 7.0 and pH 5.0, respectively. Sorption data for MIP, CA-MIP and PS-MIP were described well at the Langmuir isotherm model equilibrium. The sorption of MIP, CA-MIP and PS-MIP towards 2,4-DNP reaches equilibrium in 1 h and 2 h , respectively. The sorption of the 2,4-DNP by the MIP, CA-MIP and PS-MIP were found a better model at pseudo-second-order kinetic equation compared to first-order equation. For selectivity study, 2,4-dichlorphenol (2,4-DCP), 3-chlorophenol (3-CP) and phenol were selected as potential interferences. The sorption abilities of MIP, CA-MIP and PS-MIP for 2,4-DNP were far stronger than that of 2,4-DCP, 3-CP and phenol. The MIP could be reused after extraction with methanol: acetic acid in 2:1 (v/v) ratio and was stable for up to five sorption cycles without obvious decrease in the sorption capacity for 2,4- DNP.